THE ROLE OF TOURISTS IN INCREASING COMMUNITY INCOME IN THE SUNAN AMPEL TOURISM RELIGIOUS TOURISM AREA IN SURABAYA - Kurniawan Yunus Ariyono,; Sukma Irdiana,; Kusnanto Darmawan,; Mohammad Noor Khairullah, (Jurnal Cakrawala Ilmiah, 2023)
Religious tourism has its own charm for tourists with spiritual values and inter-religious tolerance which can be a guide for life. The history and diversity of Indonesia's natural beauty combined with spiritual values make tourist attractions have their own beauty. Indonesia has enormous potential for religious tourism. This is because Indonesia has long been known as a religious country. Many historical buildings or places have special meaning for tourists. In addition, the number of religious people in Indonesia is a potential for the development of religious tourism in Indonesia. The purpose of this research is to find out the role of tourists in increasing people's income in the religious tourism area of Sunan Ampel's tomb and to find out how the community responds to the existence of religious tourism of Sunan Ampel's tomb. Qualitative descriptive research is research that aims to describe and describe events and phenomena that occur in the field and present data in a systematic, factual and accurate manner by means of observation, interview and documentation techniques. Researchers use source triangulation to check the validity of research data, and draw conclusions. The results of this study indicate that the role of tourists in visiting religious tourism places really provides opportunities for the surrounding community to earn income. So that people around religious tourism sites can increase their income through trading religious goods.